1996
DOI: 10.1002/aic.690421112
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition of carbon on graphite by methane pyrolysis

Abstract: Chemical vapor deposition (CVD)of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Recent simulation studies [49,50] with parameter identification based on CVD [28] and CVI [30,23] experiments tend to confirm the idea that B1, B2, and C groups (see table 1) also act in the case of deposition from methane. The main difference is now that CH 4 should be considered both as a starting point for the mechanism and as a B0 group species; the formal scheme presented for propane does not have to change, only the H 2 production stoichiometries have to be revised, as well as the rate constant #1, which is considerably lower.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent simulation studies [49,50] with parameter identification based on CVD [28] and CVI [30,23] experiments tend to confirm the idea that B1, B2, and C groups (see table 1) also act in the case of deposition from methane. The main difference is now that CH 4 should be considered both as a starting point for the mechanism and as a B0 group species; the formal scheme presented for propane does not have to change, only the H 2 production stoichiometries have to be revised, as well as the rate constant #1, which is considerably lower.…”
Section: Introductionmentioning
confidence: 92%
“…Many experimental studies have shown in the past the importance of processing parameters on the pyC deposition rates and nanotexture, in various physico-chemical conditions and reactor configurations, either in CVD (plain substrate, low S V ), or in CVI (porous substrate, high S V ) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Most of them have tried to identify some "ultimate precursor" of pyC, either light, aliphatic species, or heavy aromatic compounds such as PAHs (Polycyclic Aromatic Hydrocarbons) and polyynes.…”
Section: Introductionmentioning
confidence: 99%
“…(17), which is permissible because a pseudo-steady state C profile is achieved in a short amount of time (i.e., compared to the time scale over which ⑀ changes). Note that ␣ 2 is dimensionless and that ␤ has units of inverse time.…”
Section: Formulationmentioning
confidence: 99%
“…The CVD of carbon implies that the precursor hydrocarbon, which is often methane [2][3][4], propane [5][6][7], or sometimes unsaturated hydrocarbons such as propylene [8,9] and ethylene [10][11][12], is heated to the deposition temperature, resulting in complex gas-phase reactions (homogeneous pyrolysis reactions) that are competing or interacting with complex surface reactions (heterogeneous deposition reactions). Gas-phase reactions of light hydrocarbons are synthesis reactions in which a wide variety of molecules and radicals, from the smallest species of hydrogen radical to larger species of polycyclic aromatic hydrocarbon (PAH), are formed.…”
Section: Introductionmentioning
confidence: 99%